Mapping charge transport by electroluminescence in chirality-selected carbon nanotube networks - Jakubka, Florian; Backes, Claudia; Gannott, Florentina; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Zaumseil, Jana (Acs Nano, 2013)
We demonstrate random network single-walled carbon nanotube (SWNT) field-effect transistors (FETs) in bottom contact/top gate geometry with only five different semiconducting nanotube species that were selected by dispersion with poly(9,9-dioctylfluorene) in toluene. These FETs are highly ambipolar with balanced hole and electron mobilities and emit near-infrared light with narrow peak widths (<40 meV) and good efficiency. We spatially resolve the electroluminescence from the channel region during a gate voltage sweep and can thus trace charge transport paths through the SWNT thin film. A shift of emission intensity to large diameter nanotubes and gate-voltage-dependent photoluminescence quenching of the different nanotube species indicates excitation transfer within the network and preferential charge accumulation on small band gap nanotubes. Apart from applications as near-infrared emitters with selectable emission wavelengths and narrow line widths, these devices will help to understand and model charge transport in realistic carbon nanotube networks. © 2013 American Chemical Society.